Analisis Budaya Hukum Keimigrasian Masyarakat sebagai Respon terhadap Pelanggaran oleh Orang Asing di Kecamatan Pacet Kabupaten Cianjur - Nanda Pratama, Ario; Ponco Aji, Koesmoyo; Syahrin, M. Alvi (RESEARCH FAIR UNISRI, 2025)
Pacet District, Cianjur Regency, has emerged as an attractive destination for foreign nationals, particularly from the Middle East, who are concentrated in the Villa Kota Bunga area. The presence of this community is marked by cultural acculturation and the rise of various business units, yet it is accompanied by an increase in immigration violations. This study aims to analyze the phenomenon of immigration violations by foreign nationals in Pacet and to formulate a strategy for building a legal culture as a preventive measure. The research method employed is qualitative with a normative-juridical approach, analyzing a investigation case study of a Saudi Arabian national with inicial AIT, for violating Article 122 (a) of Law No. 6 of 2011, alongside a literature review of relevant regulations and social phenomena. The findings indicate that violations, such as the misuse of stay permits for business purposes, stem from a combination of low legal awareness among both foreign nationals and the local community, as well as economic incentives that encourage illegal practices. As a solution, this study proposes a holistic strategy based on four pillars: (1) targeted legal education for foreign nationals and the local community; (2) participatory communication with local stakeholders; (3) community-based strengthening of immigration surveillance; and (4) institutional collaboration through an integrated task force. The scientific contribution of this research is a strategic framework to enhance legal compliance and reinforce state sovereignty through immigration oversight initiated at the local level. Keywords: Legal Culture; Immigration; Foreign Nationals; Stay Permit Violation; Immigration Surveillance